Pendidikan Islam di Lingkungan Keluarga Dalam Perspektif Al-Qur'an Surat As-Saffat Ayat (102) - Muhammad Farid Muhlisun; Muchotob Hamzah; Yusuf Amin Nugroho (STIKes Ibnu Sina Ajibarang, 2024)
This research aims to examine the role of Islamic education in the family environment from the perspective of the Qur'an, Surah As-Saffat verse 102. The research method used is library research with a qualitative approach. Data was obtained through the study of the Qur'an and related literature. Data collection was conducted through documentation and online data searches to gain a deeper understanding of the Islamic educational values contained in the verse. Data analysis was performed using content analysis and discourse analysis methods to identify the messages conveyed in the Qur'an.The conclusions of the research indicate that: 1) The verse emphasizes the importance of faith, patience, and obedience to religious teachings in facing life's trials. 2) It establishes a fundamental basis for forming individuals who understand religious teachings and make Islam their primary life guide. The research findings show that Islamic education in the family environment plays a crucial role in shaping the character and morals of young individuals. Surah As-Saffat verse 102 highlights the significant role of parents in educating their children according to Islamic teachings. This research contributes to increasing society's understanding of the importance of Islamic education in the family environment. It is hoped that it will serve as a reference for parents and society in providing strong and continuous religious education to future generations.